2019
DOI: 10.1177/1179597219858954
|View full text |Cite
|
Sign up to set email alerts
|

Extending Classification Algorithms to Case-Control Studies

Abstract: Classification is a common technique applied to ’omics data to build predictive models and identify potential markers of biomedical outcomes. Despite the prevalence of case-control studies, the number of classification methods available to analyze data generated by such studies is extremely limited. Conditional logistic regression is the most commonly used technique, but the associated modeling assumptions limit its ability to identify a large class of sufficiently complicated ’omic signatures. We propose a da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 50 publications
(53 reference statements)
0
32
0
Order By: Relevance
“…Stanfill et al used classification algorithms to determine the most predictive features of islet autoimmunity in the TEDDY study (504 samples) and reported adipic acid, creatinine, and leucine as influential metabolites. [44] Webb-Robertson et al used a machine learning approach to predict islet autoimmunity using data from the TEDDY study (157 case-control pairs), reporting azelaic acid and adipic acid as important features. [45] Frohnert et al predicted seroconversion to islet autoimmunity in the DAISY study (22 cases and 25 controls) and reported 3-methyl-oxobutyrate (a precursor to valine for leucine synthesis) and pyroglutamatic acid (a derivative of glutamic acid) as features that were often selected by the algorithm used.…”
Section: Discussionmentioning
confidence: 99%
“…Stanfill et al used classification algorithms to determine the most predictive features of islet autoimmunity in the TEDDY study (504 samples) and reported adipic acid, creatinine, and leucine as influential metabolites. [44] Webb-Robertson et al used a machine learning approach to predict islet autoimmunity using data from the TEDDY study (157 case-control pairs), reporting azelaic acid and adipic acid as important features. [45] Frohnert et al predicted seroconversion to islet autoimmunity in the DAISY study (22 cases and 25 controls) and reported 3-methyl-oxobutyrate (a precursor to valine for leucine synthesis) and pyroglutamatic acid (a derivative of glutamic acid) as features that were often selected by the algorithm used.…”
Section: Discussionmentioning
confidence: 99%
“…There are also 2 publications from TEDDY and 1 from the Diabetes Autoimmunity Study in the Young (DAISY) using polar metabolites to predict later islet autoimmunity. Stanfill et al used classification algorithms to determine the most predictive features of islet autoimmunity in the TEDDY study (504 samples) and reported adipic acid, creatinine, and leucine as influential metabolites ( 45 ). Webb-Robertson et al used a machine learning approach to predict islet autoimmunity using data from the TEDDY study (157 case-control pairs), reporting azelaic acid and adipic acid as important features ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conditional support vector machine (SVM) 30 was applied to develop prediction algorithms based on DS1. The reason for using “ conditional” SVM is to account for the paired structure of the matched data.…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, we centered the within pair data by its mean. 30 For example, for a specific feature, the values were 0.4 and 0.6, respectively, from the images of a case and one of his/her controls, the centered values became -0.1 and 0.1. SVM is a high-performing non-linear classifier to map input data into higher dimensional space with the purpose of better ability of data separation 31 Moreover, SVM can ignore outliers.…”
Section: Methodsmentioning
confidence: 99%